The role of personal values in the relationship between job demands and well-being among entrepreneurs - Nhuong Bui Huy; Mai Thi Thu Le; Ngoc Lan Nguyen; Susie Cox; Thuy Thi Thanh Pham; Mai Thi Thanh Bui (Asia Pacific Journal of Innovation and Entrepreneurship)
Purpose – This study aims to investigate whether personal values can moderate the relationship between entrepreneurs’ job demands and their well-being. Design/methodology/approach – The data from an email survey involving 307 entrepreneurs in the two largest cities in Vietnam were analysed. Findings – The analysis results indicated that the values of self-transcendence, openness to change and self-enhancement, which were identified as personal resources in this study, can help entrepreneurs maintain positive well-being even when they face challenging job demands in their business ventures. In contrast, conservation values reinforce the negative influence of job demands on their well-being. Practical implications – Practically, entrepreneurs are encouraged to develop certain personal values, and policymakers should endorse these values through policy proposals and amendments that facilitate entrepreneurship through education and reduced bureaucracy. Originality/value – This study further extends Conservation of Resources theory based on the mechanism that entrepreneurs use their personal values as resources to mitigate the negative impacts of the job demands of entrepreneurship on their well-being.